Fish embryo tests and acute fish toxicity tests are interchangeable in the application of the threshold approach. (13th February 2019) - Rawlings, Jane M.; Belanger, Scott E.; Connors, Kristin A.; Carr, Gregory J.
Abstract: A database was compiled for algal Organisation for Economic Co‐operation and Development (OECD) test guideline 201, for Daphnia magna OECD test guideline 202, for the acute fish toxicity (AFT) OECD test guideline 203, and for the fish embryo toxicity (FET) OECD test guideline 236 to assess the suitability and applicability of the FET test in a threshold approach context. In the threshold approach, algal and Daphnia toxicity are assessed first, after which a limit test is conducted at the lower of the 2 toxicity values using fish. If potential fish toxicity is indicated, a full median lethal concentration assay is performed. This tiered testing strategy can significantly reduce the number of fish used in toxicity testing because algae or Daphnia are typically more sensitive than fish. A total of 165 compounds had AFT and FET data available, and of these, 82 had algal and Daphnia acute toxicity data available. Algae and Daphnia were more sensitive 75 to 80% of the time. Fish or FET tests were most sensitive 20 and 16% of the time, respectively, when considered as the sole fish toxicity indicator and 27% of the time when both were considered simultaneously. When fish were the most sensitive trophic level, different compounds were identified as the most toxic in FET and to AFT tests; however, the differences were not so large that they resulted in substantially different outcomes when potencies were binned using the United Nations categories of aquatic toxicity under the Globally Harmonized System for classification and labeling. It is recommended that the FET test could be used to directly replace the AFT test in the threshold approach or could be used as the definitive test if an AFT limit test indicated toxicity potential for a chemical. Environ Toxicol Chem 2019;38:671–681. © 2019 SETAC